Colonial marine resource policy and japanese pearling activities in aru islands, 1933-1942 - Rangga Ardia Rasyid (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2023)
The Aru Islands have long been a center for The Netherlands Indies pearling industry. Its unique natural resources had positioned the island as a thriving pearl-shelling production zone. Australian-based “Celebes Trading Company” (CTC) developed the island in the image of Thursday Island pearling industry for much of the early 20th century. However as the First World War came to an end, Japanese pearling boats began to frequented the Aru waters. Even though Japanese population had been introduced as pearl labors in Aru during CTC concession, the active presence of foreign fishing vessels concerned the Dutch colonial government in the region. The island's unique natural resources have invited “unchecked movement” in the eyes of the ever-fearing Netherlands East Indies. Pursuing a more strict control over Aru Islands pearling grounds, the colonial government had to face increasingly challenging Japanese activities; dangerously testing the limits of colonial pearling management policy. With the time period situated nearing the end of Dutch colonial rule in modern Indonesia, the role of the state in dealing with such foreign threats became ambivalent as Japanese activities were seen as part of the market rivalry. But as the 1930s came to an end, military and security policy became the dominant factor in establishing colonial power in the area. By using Dutch colonial archives, this article aims to map the Netherlands East Indies responses to the rapid Japanese pearling expansion. Moreover, these responses will explore the fluid maritime frontier of Aru Islands and how it challenged the colonial constructed boundaries.